Examining Inclusive Tertiary Education Delivery through the National Open University of Nigeria's Community Study Centres - Musibau O. Oyebode (West African Journal of Open and Flexible Learning)
Conventional universities in Nigeria can no longer absorb the growing population of candidates desiring higher education. National Open University of Nigeria (NOUN) came to the rescue in 2003. With the opening of community study centres across the nation, it is pertinent to gauge access with quality. The study investigated how much access has been provided by NOUN, the adequacy of facilities, the quality of tuition, as well as attrition rate. Using the survey method involving qualitative and quantitative approaches, the instruments of data collection included a set of Likert five scale questionnaire administered to 600 respondents and an interview guide conducted with 24 interviewees selected through snowball and purposive sampling techniques. Statistical records of enrolment, registration and graduation were also analysed for attrition rate. Using Charles Wedemeyer’s theory of independent study, findings revealed that certain barriers to gaining access to tertiary education are overcome as 87.3% of the respondents believed that NOUN provides adequate access. 56.5% of the respondents adjudged NOUN facilities as inadequate while 76.5% of the respondents opined that online facilitation, video lectures and quality course materials provide good tuition. The attrition rate over six years is 41% due to personal, motivational and institutional challenges. It was concluded that though NOUN is adding value to university education in Nigeria through access and service delivery, a lot of gaps still exist. Although the community study centres are viable and have the capacity for sustenance, the government and communities need to continue collaboration with NOUN to improve their services.